ESTIMASI PROFITABILITAS BUDIDAYA TANAMAN MERANTI SEBAGAI TANAMAN TAMBAHAN DALAM KEBUN SAWIT (STUDI PADA KELOMPOK TANI SUMBER REZEKI DESA PASIR JAYA KECAMATAN RAMBAH HILIR) - SARI, RESTIKA WIDYA; -, Seprini; -, Afrizal (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2015)
The goal of this research to identify Estimasi profabilitas cultivation of meranti as additional plants in the palm garden and to know the risk of farmers in cultivation of meranti as additional plants in the palm garden. The research consist of 3 informant there are the leader of tani sumber rezeki groups, the leader bussiness development, and one member. The research used kualitatif and kuantitatif method. Kualitatif method interpret and describe the data obtained and kuantitatif method by analyze the data in table form which is then given information. Based on the result of the research estimasi profitabilitas cultivation of meranti as additional plants in the palm garden suitable estimate, but it took long time to benefit.The risk of farmer in cultivation of meranti as additional plants in the palm garden are market risk, naturals risk, production risk, and pest risk